Persistence to subcutaneous biological agents in Hungarian patients treated for inflammatory arthritis - Takacs P; Lathia U; Shin J; Nantel F (Patient Preference and Adherence, 2019)
Peter Takacs,1 Urja Lathia,2 Janey Shin,2 Francois Nantel2 1Jan-Cil Hungary, Budapest, Hungary; 2Medical Affairs, Janssen Inc., Toronto, ON, Canada Background: The aim of the study was to compare drug survival rate of subcutaneous tumor necrosis factor alpha inhibitors in rheumatoid arthritis, ankylosing spondylitis, and psoriatic arthritis patients in Hungary. Methods: This was a retrospective analysis using data collected from 5,647 patients over a period of 10 years who were treated with any of the following drugs: adalimumab (ADA), etanercept, certolizumab pegol (CZP), and golimumab (GLM). National Health Insurance Fund’s hospital, drug reimbursement, and special reimbursement registry data have been used in this study. Drug survival rate was calculated according to Kaplan–Meier survival analysis. Propensity score matching was used to reduce the potential bias caused by the inhomogeneity resulting from demographic characteristics, patient pathways, or drug administration protocols. Both raw and propensity matched data were subject of pairwise comparison between the four subcutaneous therapies. Results: The overall rate of persistence for the 4 biological therapies was between 53% and 61% after 1 year and between 14% and 19% after 4 years (follow-up time). Pairwise comparisons between therapies showed significant differences with GLM-treated patients showing longer median survival times than patients on other therapies. After propensity matching, these differences remained statistically significant between GLM and ADA or CZP over 4 years.Conclusion: Hungarian show longer persistence to GLM compared to ADA and CZP. Keywords: rheumatoid arthritis, ankylosing spondylitis, psoriatic arthritis, anti-TNF, persistence